Strategi Pengembangan Ekonomi Pedesaan melalui Inovasi Pertanian Berbasis Teknologi - Ahmad Rizky Pratama (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study explores strategies for rural economic development through technology-based agricultural innovations. The rapid advancement of digital technologies, such as precision farming, Internet of Things (IoT), and artificial intelligence (AI), has provided new opportunities for improving agricultural productivity and sustainability in rural areas. The main objective of this study is to analyze how technological innovation can enhance farmers’ income, efficiency, and competitiveness in the agricultural sector. The research uses a mixed-method approach, combining qualitative interviews with quantitative data analysis from rural farming communities in West Kalimantan. Results indicate that technological adoption, supported by government policy and digital infrastructure, significantly improves production efficiency and access to broader markets. However, barriers such as limited digital literacy and inadequate infrastructure remain critical challenges. The findings suggest that collaborative efforts among local governments, private sectors, and educational institutions are essential to support sustainable technology diffusion in rural agriculture. This research contributes to rural development studies by providing a framework for integrating technological innovation into rural economic transformation strategies.